'You've got to trust her and she's got to trust you': children's views on participation in the child protection system. Issue 1 (19th January 2014) - Cossar, Jeanette; Brandon, Marian; Jordan, Peter
Abstract: Participation by children in child protection remains a complex area of practice. This paper presents findings from a qualitative study exploring the views of 26 children, aged 6–17 years, about their participation in the child protection system in England. All of the children were subject to a child protection plan and were living at home at the time of interview. The children's understanding of the child protection process was categorized, and the majority of children, including the youngest, were found be at least partially aware of the child protection process, often struggling to make sense of the professional intervention in their families on the basis of partial information. It is argued that decisions about children's involvement should take into account not only children's age and understanding, but be seen in the context of wider family dynamics. Participation in formal processes such as child protection conferences was experienced as difficult and emotive. The child's relationship with their social worker was central to meaningful participation.